Children's ability to answer different types of questions*. Issue 2 (22nd March 2012) - SALOMO, DOROTHÉ; LIEVEN, ELENA; TOMASELLO, MICHAEL
ABSTRACT: Young children answer many questions every day. The extent to which they do this in an adult-like way – following Grice's Maxim of Quantity by providing the requested information, no more no less – has been studied very little. In an experiment, we found that two-, three- and four-year-old children are quite skilled at answering argument-focus questions and predicate-focus questions with intransitives in which their response requires only a single element. But predicate-focus questions for transitives – requiring both the predicate and the direct object – are difficult for children below four years of age. Even more difficult for children this young are sentence-focus questions such as "What's happening?", which give the child no anchor in given information around which to structure their answer. In addition, in a corpus study, we found that parents ask their children predicate-focus and sentence-focus questions very infrequently, thus giving children little experience with them.